(untitled) (Clinics, 2023)
Background: Clinical reports associate kidneys from female donors with worse prognostic in male recipients. Brain Death (BD) produces immunological and hemodynamic disorders that affect organ viability. Following BD, female rats are associated with increased renal inflammation interrelated with female sex hormone reduction. Here, the aim was to investigate the effects of sex on BD-induced Acute Kidney Injury (AKI) using an Isolated Perfused rat Kidney (IPK) model. Methods: Wistar rats, females, and males (8 weeks old), were maintained for 4h after BD. A left nephrectomy was performed and the kidney was preserved in a cold saline solution (30 min). IPK was performed under normothermic temperature (37°C) for 90 min using WME as perfusion solution. AKI was assessed by morphological analyses, staining of complement system components and inflammatory cell markers, perfusion flow, and creatinine clearance. Results: BD-male kidneys had decreased perfusion flow on IPK, a phenomenon that was not observed in the kidneys of BD-females (p < 0.0001). BD-male kidneys presented greater proximal (p = 0.0311) and distal tubule (p = 0.0029) necrosis. However, BD-female kidneys presented higher expression of eNOS (p = 0.0060) and greater upregulation of inflammatory mediators, iNOS (p = 0.0051), and Caspase-3 (p = 0.0099). In addition, both sexes had increased complement system formation (C5b-9) (p=0.0005), glomerular edema (p = 0.0003), and nNOS (p = 0.0051). Conclusion: The present data revealed an important sex difference in renal perfusion in the IPK model, evidenced by a pronounced reduction in perfusate flow and low eNOS expression in the BD-male group. Nonetheless, the upregulation of genes related to the proinflammatory cascade suggests a progressive inflammatory process in BD-female kidneys.